Pengenalan Visualisasi Programming untuk Membuka Pintu Kecerdasan Teknologi Anak SD Pesisir - Rifai, Sitti Najmia; Rauf, Budi Wijaya; Yasin, Muhammad Akbar; Syahib, Muhammad Irwan; Ilcham, Ilcham (Anoa : Jurnal Pengabdian Masyarakat Fakultas Teknik, 2023)
Increasing technological intelligence in elementary school children is a necessity in this digital era. Therefore, this research explores the application of programming visualization using the Scratch application as an innovative method in supporting programming learning for elementary school children. Through a visual programming block approach, Scratch provides a fun and intuitive learning experience, helping children to develop an understanding of basic programming concepts. This study involved a group of elementary school children as participants, and tracked the development of their understanding of programming logic and creativity through interactive activities in Scratch. The research results show that the application of Scratch significantly increases children's grasp of programming concepts, while stimulating their creativity.